Effect of playing on anxiety of hospitalized school age children - yasaman yaghoobi; zahra shafipour; zahra atrkar roushan; jafar modaber nia (Journal of Holistic Nursing and Midwifery)
Introduction: Anxiety is one of the most common reactions to stressors and ‎hospitalized children confront it and playing is a priority care to reduce stress.‎